Bewegung – Spielraum für Bildung: Chancen für bereichsbezogenes Lernen in der frühen Kindheit - Brandes, Björn; Erhorn, Jan; Schwier, Jürgen (transcript, 2020)
Why movement in early childhood serves as a medium and motor for various areas of development and plays a central role in processes of self- and environmental development.